IKEA entry - Effects on firms in retail and hospitality - Helena Nilsson (Institute of Retail Economics (HFI), 2020)
This study examines the entry effects of a durable goods big box, IKEA, on incumbent firms in the retail, accommodation and restaurant sectors in Sweden. Using a difference-in-difference approach combined with matching, the effects of IKEA entry on the net turnover and employment of incumbent firms located at varying distances from the new IKEA store are examined. The results show that entry by IKEA increases the net turnover of retail firms near the entry site that sell complement goods, indicating that IKEA entry causes demand spillovers due to multipurpose shopping. IKEA entry also increases the net turnover of accommodation firms in the region, which indicates that the entrant has a positive effect on the attractivity of the area. The estimations reveal no effects on retail firms located in the affected city centers, which suggests that retail in central places may have a certain resilience to competition from out-of-town retail clusters. No robust effects on substitute goods retailers or restaurants are found.
Keywords: C33; D22; L81; L83; 330; IKEA; retail; hospitality; agglomeration economies; competition; difference-in-difference